A SURVEY OF ACCIDENTS IN CONSTRUCTION MANAGEMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Construction industry has become most hazardous industry in last three decade, because of the need to grow vertically. As there is no space on left on ground, the need of growing vertically arises. This has emerged as a competition amongst world renowned builders and countries to build the tallest tower in our country. It is been observed that many precaution are to be taken while building a tallest tower. Still construction manager cannot ensure, there will be zero accident. As many workers are involved from different background, as for many of the cases does not require a prior knowledge or education for some of the task in construction industry. All over the world, developing has poor record for construction site safety.